Rapid Versus Laboratory-Based Testing for HIV and Hepatitis C at a Drug Detoxification Treatment Center: A Randomized Trial. (2nd September 2020) - Assoumou, Sabrina A; Paniagua, Samantha M; Linas, Benjamin P; Wang, Jianing; Samet, Jeffrey H; Hall, Jonathan; White, Laura F; Beckwith, Curt G
Abstract: Background: A health department survey revealed nearly half employ laboratory-based HIV and HCV testing (LBT) over rapid testing (RT) in nonhospital settings such as drug detoxification centers. LBT has higher sensitivity for acute HIV infection compared to RT but LBT is not point of care and may result in fewer diagnoses due to loss to follow-up before result delivery. Methods: We conducted a randomized trial comparing real-world case notification of RT (Orasure) vs LBT (HIV Combo Ag/Ab EIA, HCV EIA) for HIV and HCV at a drug detoxification center. Primary outcome was receipt of test results within 2 weeks. Results: Among 341 individuals screened (11/2016–7/2017), 200 met inclusion criteria; 58% injected drugs and 31% shared needles in the previous 6 months. Of the 200 randomized, 98 received RT and 102 LBT. Among all participants, 0.5% were positive for HIV and 48% for HCV; 96% received test results in the RT arm and 42% in the LBT arm (odds ratio, 28.72; 95% confidence interval, 10.27–80.31). Real-world case notification was 95% and 93% for HIV and HCV RT, respectively, compared to 42% for HIV and HCV LBT. Conclusions: RT has higher real-world case notification than LBT at drug detoxification centers. Clinical trials registration: NCT02869776.